Window, Marshall Sons and Co. building - Ghosh, Ayan (2023)
Keystone with floral scrolls emerging from it over oeil-de-boeuf (Ox eye window) at the Marshall Sons and Co. building. The use of exaggerated keystones was a typical Neo-Baroque architectural detail used in buildings from the Edwardian era (1901–1910).